Risk profile of young people admitted to hospital for suicidal behaviour in Melbourne, Australia. (20th May 2018) - Borschmann, Rohan; Stark, Patrick; Prakash, Chidambaram; Sawyer, Susan M
Abstract : Aim: Self‐harm and suicidal behaviour is most prevalent during adolescence, but little is known about the risk profile of adolescents admitted to hospital for suicidal behaviour. Young people who self‐harm are at an increased risk of mortality compared to those who do not self‐harm; adolescents admitted to hospital for suicidal behaviour are particularly at risk. The aim of this study was to generate a risk profile of adolescents admitted to hospital with suicidal behaviour. Methods: We conducted a 12‐month retrospective audit of adolescent admissions to the mental health inpatient unit at a tertiary children's hospital in Melbourne, Australia. Routinely collected data were used to generate a risk profile. Results: We found that 212 of 271 (78.2%) admissions were due to suicidal behaviour. Of these, 107 (51%) adolescents were diagnosed with one or more mental disorders at discharge, most commonly major depressive disorder. Beyond known distal determinants of health risk, the proximal risk profile of these adolescents included factors relating to gender, substance use, prior mental health diagnoses and prior admission to hospital. Poor sleep was also a risk factor, with 159 (75%) reporting a recent history of sleeping problems. Conclusions: The very high proportion of admissions to the mental health inpatient unit due to suicidal behaviour reinforces the importance of finding effective methods of identification of the risk processes underpinning suicidal behaviours to reduce the unnecessary waste of young lives by suicide.